Factores de riesgo en membrana Hialina en el Área de Neonatología del Hospital Isidro Ayora Loja - Murillo Jaramillo, María José (2020)
The Hyaline Membrane disease, it constitutes a high mortality rate in newborns throughout and it represents 1.24% of the causes of infant mortality according to the figures from (INEC, 2014). The present investigation is important since it allows to know and identify the risk factors of this pathology and thus contribute to reducing the neonatal morbity and mortality rate for an effective and early reduction by detecting the factors that predispose to the appearance of this disease. The objective of this investigation is to determinate the most prevalent risk factors in the hyaline membrane of newborns of Isidro Ayora Hospital´s neonatal area in Loja City. A transversal, analytical and prospective study was done, whose population was taken in a 6-month period consisting of 99 newborns diagnosed with Hyaline membrane in the neonatology area of that hospital, the sample corresponds to the study universe, the technique was the collection of data from the clinical records of the newborn and the mother, obtaining the results: A maternal age less than 20 years (38.38%), urinary tract infections (58.59) associated with the lack of administration of antenatal corticosteroids (87.12%) with neonates with a very low birth weight < 1500gr (50.50%). Keyword: Premature, Risk, Respiratory.